Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the value of the slope [tex]\( m \)[/tex] such that the line [tex]\( y = mx - 3 \)[/tex] is tangent to the parabola [tex]\( y = 3x^2 - x \)[/tex], we need to determine the condition under which the line only intersects the parabola at a single point. This typically involves solving the system of equations given by setting the two expressions for [tex]\( y \)[/tex] equal to each other and ensuring that the resulting quadratic equation has exactly one solution (i.e., its discriminant is zero).
### Step-by-Step Solution
1. Set the equations equal to each other:
[tex]\[ mx - 3 = 3x^2 - x \][/tex]
2. Rearrange the equation to standard quadratic form:
[tex]\[ 3x^2 - (m + 1)x + 3 = 0 \][/tex]
3. Identify the coefficients of the quadratic equation:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
Comparing with the standard form, we have:
[tex]\[ a = 3, \quad b = -(m + 1), \quad c = 3 \][/tex]
4. Recall the formula for the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
5. Substitute the coefficients into the discriminant formula:
[tex]\[ \Delta = [-(m + 1)]^2 - 4 \cdot 3 \cdot 3 \][/tex]
6. Simplify the discriminant:
[tex]\[ \Delta = (m + 1)^2 - 36 \][/tex]
7. For the line to be tangent to the parabola, the discriminant must be zero:
[tex]\[ (m + 1)^2 - 36 = 0 \][/tex]
8. Solve for [tex]\( m \)[/tex]:
[tex]\[ (m + 1)^2 = 36 \][/tex]
9. Take the square root of both sides:
[tex]\[ m + 1 = \pm 6 \][/tex]
10. Solve the resulting equations:
[tex]\[ m + 1 = 6 \quad \text{or} \quad m + 1 = -6 \][/tex]
[tex]\[ m = 5 \quad \text{or} \quad m = -7 \][/tex]
### Conclusion
The slopes [tex]\( m \)[/tex] for which the line [tex]\( y = mx - 3 \)[/tex] is tangent to the parabola [tex]\( y = 3x^2 - x \)[/tex] are [tex]\( \boxed{5 \text{ and } -7} \)[/tex].
### Step-by-Step Solution
1. Set the equations equal to each other:
[tex]\[ mx - 3 = 3x^2 - x \][/tex]
2. Rearrange the equation to standard quadratic form:
[tex]\[ 3x^2 - (m + 1)x + 3 = 0 \][/tex]
3. Identify the coefficients of the quadratic equation:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
Comparing with the standard form, we have:
[tex]\[ a = 3, \quad b = -(m + 1), \quad c = 3 \][/tex]
4. Recall the formula for the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
5. Substitute the coefficients into the discriminant formula:
[tex]\[ \Delta = [-(m + 1)]^2 - 4 \cdot 3 \cdot 3 \][/tex]
6. Simplify the discriminant:
[tex]\[ \Delta = (m + 1)^2 - 36 \][/tex]
7. For the line to be tangent to the parabola, the discriminant must be zero:
[tex]\[ (m + 1)^2 - 36 = 0 \][/tex]
8. Solve for [tex]\( m \)[/tex]:
[tex]\[ (m + 1)^2 = 36 \][/tex]
9. Take the square root of both sides:
[tex]\[ m + 1 = \pm 6 \][/tex]
10. Solve the resulting equations:
[tex]\[ m + 1 = 6 \quad \text{or} \quad m + 1 = -6 \][/tex]
[tex]\[ m = 5 \quad \text{or} \quad m = -7 \][/tex]
### Conclusion
The slopes [tex]\( m \)[/tex] for which the line [tex]\( y = mx - 3 \)[/tex] is tangent to the parabola [tex]\( y = 3x^2 - x \)[/tex] are [tex]\( \boxed{5 \text{ and } -7} \)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.